2018
DOI: 10.1038/s41563-018-0118-1
|View full text |Cite
|
Sign up to set email alerts
|

Coupling two order parameters in a quantum gas

Abstract: Controlling matter to simultaneously support coupled properties is of fundamental and technological importance (for example, in multiferroics or high-temperature superconductors). However, determining the microscopic mechanisms responsible for the simultaneous presence of different orders is difficult, making it hard to predict material phenomenology or modify properties. Here, using a quantum gas to engineer an adjustable interaction at the microscopic level, we demonstrate scenarios of competition, coexisten… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 29 publications
0
25
0
1
Order By: Relevance
“…The organized state may be called a 'density-wave polariton condensate' in recognition of the joint light-matter-wave nature of the quasiparticles in the macroscopically occupied and coherent density-photon mode [37]. Roton instabilities and the extended Bose-Hubbard model have been realized [38][39][40], and similar systems employing a few degenerate cavity modes have created a supersolid [41], an intertwined spatial order [42], and supermode-densitywave polariton condensates [37]. Highly degenerate cavities have been used to engineer tunable-range photon mediated atom-atom interactions [43] that may lead to liquid crystalline states [44].…”
mentioning
confidence: 99%
“…The organized state may be called a 'density-wave polariton condensate' in recognition of the joint light-matter-wave nature of the quasiparticles in the macroscopically occupied and coherent density-photon mode [37]. Roton instabilities and the extended Bose-Hubbard model have been realized [38][39][40], and similar systems employing a few degenerate cavity modes have created a supersolid [41], an intertwined spatial order [42], and supermode-densitywave polariton condensates [37]. Highly degenerate cavities have been used to engineer tunable-range photon mediated atom-atom interactions [43] that may lead to liquid crystalline states [44].…”
mentioning
confidence: 99%
“…A theoretical description of the phase boundaries revealed that an antisymmetric coupling to the P band of the pump lattice induces self-organization. This different lattice geometry for ∆ a > 0 could further lead to a qualitatively different coupling behavior in two-or multi-mode scenarios [17,32]. The observed cycling dynamic appears qualitatively in the phase diagram where limit cycles, chaos, and time crystal behavior were theoretically predicted in related models [26][27][28].…”
mentioning
confidence: 91%
“…The last ten years have witnessed swift progress in quantum optics platforms where light and matter are strongly coupled and can be employed to engineer a variety of quantum phenomena: examples range from Bose-Einstein condensates coupled to optical cavity photons, where the Dicke transition is engineered [1,2], to the recent demonstration of supersolids [3] and phases with competing order parameters in a condensate trapped at the intersection of two optical cavities [4][5][6][7]. Most of these models realise scenarios where matter and light collectively interact as in the case of superradiant phase transitions or in 'Dicke-Hubbard' systems characterized by critical points separating a superfluid from a Mott insulating phase [8].…”
Section: Introductionmentioning
confidence: 99%